Detection and control of an ongoing international outbreak of hepatitis A among the Irish Traveller community beginning September 2020. (16th February 2022) - Kelly, David; O'Hare, Colette; McKeown, Paul; Cianci, Fiona; Doyle, Sarah
Abstract: Hepatitis A virus (HAV) infection is a notifiable disease in Ireland, with national coverage of clinical and laboratory surveillance. In December 2020, a cluster of 11 HAV cases among the Irish Traveller community was detected. The outbreak investigation identified 61 total HAV cases from September 2020 to November 2021. Sequenced isolates were sub-genotype IA with identical genome sequence. Case-patients were predominantly aged under 18 (77%), hospitalised (46%) and lived on communal residential sites. Mass onsite HAV vaccination was employed following failure of initial ring vaccination to contain the outbreak. This is the largest outbreak of HAV described in Ireland, involving spillover to the UK and Netherlands. We recommend mass HAV vaccination and tailored communication for outbreak control in migratory subpopulations.